Fabrication of metallic and non-metallic top electrodes for large-area molecular junctions. Issue 20 (7th April 2021) - Gorenskaia, Elena; Turner, Kelly L.; Martín, Santiago; Cea, Pilar; Low, Paul J.
Abstract : This Review presents an overview of methods used to deposit top-contact electrodes on electrode-supported monolayers to create 'large area' molecular junctions, highlighting the challenges and solutions identified to date. Abstract : Molecular junctions have proven invaluable tools through which to explore the electronic properties of molecules and molecular monolayers. In seeking to develop a viable molecular electronics based technology it becomes essential to be able to reliably create larger area molecular junctions by contacting molecular monolayers to both bottom and top electrodes. The assembly of monolayers onto a conducting substrate by self-assembly, Langmuir–Blodgett and other methods is well established. However, the deposition of top-contact electrodes without film penetration or damage from the growing electrode material has proven problematic. This Review highlights the challenges of this area, and presents a selective overview of methods that have been used to solve these issues.